Pragmatic engineering and lifestyle : responsible engineering for a sustainable future - Ting, David S-K; Stagner, Jacqueline A. (Emerald Publishing Limited, 2023)
The most productive way to engage society as a whole with issues of sustainability is to involve them in the development and execution of the solutions. Pragmatic Engineering and Lifestyle draws together international experts from engineering and architecture to disclose the latest insights into forging viable means to sustain tomorrow's needs. Focusing on breaking through the remaining barriers and fully realizing promising remedies by explicitly examining the social aspect of engineering and urban design, the authors present state of the art research on, among other topics, simple and responsible engineering and living, ecological and socially friendly buildings and infrastructures, socially resilient farming, and agroecology. Pragmatic Engineering and Lifestyle is an indispensable collection for tomorrow's engineers, architects, and policy makers.
Keywords: Sustainable engineering.; Technology & Engineering -- Environmental -- General.; Engineering: general.; elektronické knihy; electronic books